Effectiveness of Nursing Counseling on Psycho-social Burdens of women after Mastectomy - Rusul S. Ghazal; Iqbal M. Abbas (Journal of Madenat Alelem University College, 2013)
In surveys of the last 10 years, an increase has been reported in particular in breast surgery for breast cancer. Breast cancer can cause serious psychological problems due to many factors such as uncertainty in treatment, physical symptoms, fear of recurrence and death. To identify the effectiveness of nursing counseling on Psycho-social Burdens on women after mastectomy, a quasi-experimental design conducted on non-probability (purposive) sample of thirty women who had received a mastectomy as an intervention group selected during period from 2nd August to 10th November 2011. The study was conducted at three hospitals in Baghdad which considered the main settings that provided health care for the patients from all types of cancer. Baseline data collection (pre-test), Post-test1 and Post-test2 took place and application of the nursing counseling on Psycho-social burdens after mastectomy. The questionnaire form is consisted of two parts which included demographic and reproductive characteristics, and Psycho-social burdens after mastectomy. Content validity and reliability of the questionnaire determined through a pilot study, descriptive and inferential statistic is used to analyze the data. Results of the study showed that the highest of study sample 36.7 % were in age group (50-60) years old, 53.3% their age at menarche were 13-14 years old. The highest percentages of study group 46.7% their age at married were 20-24 years old. The highest mean of score related to the psycho-social burdens were referred to the thinking, anxiety, positive behavior, and sexual burdens. Highly significant differences had been obtained for the three matching (pre-post1, pre-post2, and post1-post2) related to psychological burdens, highly significant differences had been recorded for the two matched of testing (pre-post1, and pre-post2) except with the third matched (post1-post2) no significant differences was obtained related to the spiritual aspect, social and sexual burdens.